Residential Satisfaction for a Continuum of Households: Evidence from European Countries - Riccardo Borgoni; Alessandra Michelangeli; Federica Pirola (Global Labor Organization (GLO), 2018)
Residential satisfaction depends on housing and neighborhood conditions in addition to housing cost affordability. To determine the relative importance of these factors, their average effect is usually estimated using sample data, eventually split in sub-samples in order to represent social classes. In this paper, within the theoretical framework of subjective well-being, we propose a novel empirical strategy independent of the concept of social class, able to estimate how the effect of drivers of residential satisfaction change on continuous according to households' income. We apply our methodology to investigate residential satisfaction in 23 European countries using 2012 EU-SILC module on housing conditions.
Keywords: R11; R12; R23; 330; housing; subjective well-being; Europe; EU-SILC Survey